En Bloc Kidney Transplantation: A Retrospective Study of an 18-year Experience in a Single Institution - Emilien Seizilles de Mazancourt; Lionel Badet; Ricardo Codas Duarte; Emmanuel Morelon; Sebastien Crouzet; Nicolas Terrier; Xavier Matillon (European Urology Open Science, 2022)
Background: Renal transplantation is facing a shortage of grafts. En bloc kidney transplantation (EBKT) from pediatric donors could increase the number of available grafts. Objective: To describe the surgical technique as well as the long-term functional and morphological results of EBKT. Design, setting, and participants: We performed a retrospective study of all the EBKT procedures performed in Lyon between 2002 and 2020. Electronic medical records were checked with an analysis of demographics, and peri- and postoperative results. Outcome measurements and statistical analysis: A descriptive analysis of donor and recipient characteristics, perioperative data, complications, and renal function was performed. Results and limitations: Between 2002 and 2020, 21 EBKT procedures were performed. Donors had a mean weight of 8.6 kg and a mean age of 12 mo, with a mean cold ischemia time of 11 h and 30 min. Receivers had a mean age of 30 yr and a body mass index of 20. The mean follow-up time was 62 mo, with patient survival of 100% and graft survival of 95%. There were 13 reinterventions comprising one early unilateral transplantectomy for thrombosis. Renal function was excellent, and the morphological findings described an important growth in size in the first 2 yr before attaining the adult size. This study’s limitations include its retrospective nature and a small number of participants. Conclusions: The present study reports excellent results with EBKT and supports the pursuit and spread of this technique. Patient summary: In this report, we describe the technique and results of en bloc kidney transplantation. We found that results are excellent for renal function and patient survival. We conclude that en bloc kidney transplantation should be considered to increase the number of grafts.